2019
DOI: 10.1061/(asce)ww.1943-5460.0000514
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Impulse Wave Generation and Propagation

Abstract: Rapid landslides into water bodies may generate massive water waves posing a threat to riparian settlements and infrastructure. These waves are referred to as impulse waves and exhibit tsunami-like characteristics. The generation and in particular the spatial propagation of impulse waves was studied in a hydraulic laboratory wave basin. A videometric measurement system was applied to track the water surface displacement. Compared to fixed wave gauges typically applied in previous studies, this technique yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…the measured impulse wave celerities mainly scatter between 95% and 103% of the solitary wave celerity. This agrees with the findings by McFall and Fritz [23] and Evers et al [24] for spatial impulse wave propagation in wave basins. The relative wave length L/h of Müller's [7] experiments range between 9 and 56.…”
Section: Datasetssupporting
confidence: 93%
“…the measured impulse wave celerities mainly scatter between 95% and 103% of the solitary wave celerity. This agrees with the findings by McFall and Fritz [23] and Evers et al [24] for spatial impulse wave propagation in wave basins. The relative wave length L/h of Müller's [7] experiments range between 9 and 56.…”
Section: Datasetssupporting
confidence: 93%
“…Considering only the parameters imposed by the topography, large drop heights and steep slope angles induce high slide velocities. Based on experiments in a wave basin, Evers et al (2019a) found the slide width to be an additional governing parameter for 3D wave generation and propagation: The wider a slide, the larger the wave.…”
Section: Tsunami Generation By Saemmmentioning
confidence: 99%
“…While a first wave is generated due to the direct impact of the slide, it may be followed by several further waves due to the drawdown and run-up along the shore after the initial impact. Such series of multiple wave crests and troughs are referred to as impulse wave trains (Mohammed and Fritz 2012;McFall and Fritz 2016;Evers et al 2019a). As the initial wave heights can be significantly larger than those of earthquake-induced tsunamis, such waves are also known as megatsunamis.…”
Section: Motivationmentioning
confidence: 99%
“…McFall and Fritz (2016) came to similar results, with the second wave being on average 23% slower than the first wave. Evers et al (2019a) compared the measured first and second wave crest celerity with the solitary wave celerity cSol and found that on average c1 = 0.95cSol and c2 = 0.7cSol, respectively. This matches well with the present findings, for which the wave crest celerity of wave i within the wave train may be predicted by ,…”
Section: Impulse Wave Trainsmentioning
confidence: 99%
See 1 more Smart Citation